From bimetallism to monetarism: The shifting political affiliation of the quantity theory - David Laidler (The University of Western Ontario, Department of Economics, 2001)
The quantity theory of money was associated with the politics of the right in the '70s and '80s, but a century earlier, particularly in America, it had played an important part in the proposals of the Progressive left. These political associations are examined, and it is argued that a crucial factor in the quantity theory's apparent migration from left to right was its newly-forged links to the case for monetary policy rules in the interwar years. It was also in the 1930s that the endogenous-money Banking School doctrines deployed by anti-quantity theorists during the monetarist controversy first became mainly associated with the case for discretionary policy, rather than with support for the gold-standard rule, as they had been in earlier times. More generally, shifting scientific opinion about the causes of the Great Depression moved the political centre of gravity of monetary economics to the left from the 1930s onwards, and then back towards the right beginning in the '60s, creating an illusion of movement on the quantity theory's part.
Keywords: 330; Quantitätstheorie; Währungswettbewerb; Monetarismus; Dogmengeschichte